TRAINING ON E-MODULE COMPILATION BASED ON PjBL WITH A STEM APPROACH TO DEVELOP THE NUMERACY LITERACY ABILITY OF MATHEMATICS TEACHERS IN DONGGALA DISTRICT - Pathuddin, Pathuddin; Ningsih, Purnama; Afadil, Afadil; Rahmawati, Sitti; Ahmar, Dewi Satria (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
E-modules or electronic modules are non-printing digital modules that are developed with special computer-assisted applications, and multimedia elements are provided to make them more attractive and interactive. To make the module more interesting, teachers also need innovation in developing modules, namely modules based on approaches, methods or models. One that can be developed is combining the PjBL learning model with the STEM approach. The combination of the application of the STEM approach with the project-based learning (PjBL) learning model can encourage cooperation between educational institutions and industry. The PjBL model emphasizes project-based learning with a STEM approach that requires integration between natural science, technology, engineering, and mathematics. The combination can develop critical, creative, and collaborative thinking skills in their students. However, the reality in the field based on interviews with the head of the Donggala district mathematics MGMP, there is no e-module for mathematics learning based on PjBL with a STEM approach for teachers and students in Donggala Regency. Teachers who are members of the Mathematics Subject Teacher Conference (MGMP) as partners of this service are still experiencing problems in making modules / e-modules that are interestingly interactive and link them to learning approaches and models. These problems are caused by various factors, including members of the Donggala district mathematics MGMP who do not understand: 1) the principles of interesting and interactive e-module design, 2) techniques for making PjBL-based e-modules with a STEM approach, 3) techniques for designing and implementing effective project-based learning (PjBL) and combining science, technology, engineering, and mathematics in chemistry learning (STEM). The solution offered to overcome the partner's problems is to provide workshops/training: 1) the principles of attractive and interactive e-module design, 2) making PjBL-based e-modules with a STEM approach, 3) how to analyze and interpret mathematics materials related to project-based learning (PjBL, as well as analysis of mathematics materials related to science, technology, engineering, and mathematics and their incorporation techniques in mathematics learning (STEM) The purpose of this service activity is to overcome partner problems in compiling and developing PjBL-based e-modules with a STEM approach so as to improve the numeracy-literacy skills of teachers who are members of the Donggala district mathematics MGMP. The outputs that have been achieved are that the members of the partner group have made PjBl-based e-modules with a STEM approach so that there is an increase in their numeracy literacy skills and publish the e-modules and process them into the form of PjBl-based books / modules with a STEM approach that has an ISBN and HaKi.